Analysis of the Interaction Network of Hub miRNAs-Hub Genes, Being Involved in Idiopathic Pulmonary Fibers and Its Emerging Role in Non-small Cell Lung Cancer - Yu, Dong Hu; Ruan, Xiao-Lan; Huang, Jing-Yu; Liu, Xiao-Ping; Ma, Hao-Li; Chen, Chen; Hu, Wei-Dong; Li, Sheng (Frontiers in Genetics, 2020)
Idiopathic pulmonary fibrosis (IPF) is a fibrotic interstitial lung disease with lesions confined to the lungs. To identify meaningful microRNA and gene modules related to the IPF progression, RNA-sequencing data of GSE32537 and miRNA-sequencing data of GSE32538 were subjected to weighted gene co-expression network analysis (WGCNA). GSE10667, GSE70866 and GSE27430 were utilized to validate the results and characterize the clinical significance of the genes and the miRNAs. Six hub genes (COL3A1, COL1A2, OGN, COL15A1, ASPN and MXRA5) and seven hub miRNAs (hsa-let-7b-5p, hsa-miR-26a-5p, hsa-miR-25-3p, hsa-miR-29c-3p, hsa-let-7c-5p, hsa-miR-29b-3p and hsa-miR-26b-5p) were clarified and validated. Meanwhile, iteration network of hub genes-hub miRNAs was constructed, and the emerging role of the network being involved in non-small cell lung cancer (NSCLC) was also been analyzed by several webtools. The levels of the hub genes expression were different between normal lung tissues and NSCLC tissues. Six genes (COL3A1, COL1A2, OGN, COL15A1, ASPN and MXRA5) and three miRNAs (hsa-miR-29c-3p, hsa-let-7c-5p and hsa-miR-29b-3p) were associated with the survival time of lung adenocarcinoma. The interaction network of hub miRNAs-hub genes might provide common mechanisms involving in IPF and NSCLC. More importantly, new clues were identified in developing therapeutic strategies for both diseases based on novel molecular advances.